Exercise Diminishes Plasma Neurofilament Light Chain and Reroutes the Kynurenine Pathway in Multiple Sclerosis. Issue 3 (May 2021) - Joisten, Niklas; Rademacher, Annette; Warnke, Clemens; Proschinger, Sebastian; Schenk, Alexander; Walzik, David; Knoop, Andre; Thevis, Mario; Steffen, Falk; Bittner, Stefan; Gonzenbach, Roman; Kool, Jan; et al.
Abstract : Objective: To examine acute (single-bout) and training effects of high-intensity interval training (HIIT) vs standard exercise therapy (moderate continuous training [MCT]) on plasma neurofilament light chain (pNfL) and kynurenine (KYN) pathway of tryptophan degradation metabolites in persons with multiple sclerosis (pwMS). Methods: Sixty-nine pwMS (Expanded Disability Status Scale score 3.0–6.0) were randomly assigned to a HIIT or an MCT group. Changes in pNfL and KYN pathway metabolites measured in blood plasma were assessed before, after, and 3 hours after the first training session as well as after the 3-week training intervention. Results: Acute exercise reduced pNfL and increased the KYN pathway flux toward the neuroprotective kynurenic acid (KA). Changes in pNfL correlated positively with changes in KA and negatively with the quinolinic acid-to-KA ratio. HIIT consistently led to greater effects than MCT. Following the 3-week training intervention, the KYN pathway was activated in HIIT compared with MCT. Conclusion: Future studies and clinical assessments of pNfL should consider acute exercise as confounding factor for measurement reliability. Moreover, exercise-induced KYN pathway rerouting might mediate neuroprotection, potentially underlying the benefits in rehabilitation for pwMS. Classification of Evidence: This study provides Class II evidence that acute HIIT diminishes pNfL and increases KA levels, and 3 weeks of HIIT activate the KYN pathway in pwMS. Trial Registration Information: Clinical trial registration number: NCT03652519.